Performance Evaluation of Modulated Markov Process Models for Traffic on IEEE 802.11 Networks – Study of Case for the QRD Network (2019)
This paper evaluates the performance of Markov modulated processes models in IEEE 802.11 networks. This study is focused on the “Quindio Región Digital” (QRD) network. Performance evaluation of the traffic models is performed in three stages. In the first stage, we obtain the statistical characteristics of the current traffic on the QRD network. In the second stage, the most suitable traffic models are selected for the current characteristics of the QRD network such asout-of-saturation operation and management of heterogeneous traffic. In the third stage, we define a performance metric that is used to evaluate the traffic patterns through simulation.